Quand comparaison juridique n’est pas raison politique. Les juristes britanniques et canadiens-français comme analystes des systèmes de common law et de droit civil en amont de l’Acte de Québec (1774) - David Gilles (Clio@Themis)
The conquest of Canada by the British in 1759-1763 opened a period of intense change and a degree of legal and institutional excitement. In the space of 15 years, several orientations were taken, requiring a comparative assessment of French and English law to build the legal future of the new British colony. Up until the Quebec Act, legal scholars of British and French origin analyzed and compared the merits of these two legal models – strongly criticized each other – until finding a compromise solution allowing for an adaptation of the law, and an appropriation of identity typical of the colonial legal approach, thus identifying a true Legal transplant.